Effect of zinc deficiency on chronic kidney disease progression and effect modification by hypoalbuminemia. - Atsuyuki Tokuyama (Public Library of Science (PLoS), 2021)
Serum zinc (Zn) levels tend to be low in chronic kidney disease (CKD) patients. This cohort study was conducted to investigate the relationship between zinc deficiency and CKD progression. Patients were classified into two groups based on Zn levels < 60 μg/dl (low-Zn group, n = 160) and ≥ 60 μg/dl (high-Zn group, n = 152). The primary outcome was defined as end-stage kidney disease (ESKD) or death and was examined over a 1-year observation period. Overall, the mean Zn level was 59.6 μg/dl and the median eGFR was 20.3 ml/min/1.73 m2. The incidence of the primary outcome was higher in the low-Zn group (p<0.001). Various Cox proportional hazards models adjusted for baseline characteristics showed higher risks of the primary outcome in the low-Zn group than in the high-Zn group. Competing risks analysis showed that low Zn levels were associated with ESKD but not with death. Moreover, in propensity score-matched analysis, the low-Zn group showed a higher risk of the primary outcome [adjusted hazard ratio 1.81 (95% confidence interval 1.02, 3.24)]. Furthermore, an interaction was observed between Zn and serum albumin levels (interaction p = 0.026). The results of this study indicate that zinc deficiency is a risk factor for CKD progression.